DETERMINANTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Yopi Yulius (Dinasti Publisher, 2022)
This study aims to examine the effect of Organizational Commitment and Work Satisfaction on Organizational Citizenship Behavior. This study uses explanatory quantitative research on 20 manufacturing company in West Java with 70 respondents processed using the SEM-PLS approach. The results of the study indicate that Organizational Commitment directly influences Organizational Citizenship Behavior manufacturing company in West Java and Work Satisfaction directly influence Organizational Citizenship Behavior manufacturing company in West Java.